Post-earthquake fast damage assessment using residual displacement and seismic energy: Application to Mexico City. Issue 4 (November 2021) - Quinde, Pablo; Terán-Gilmore, Amador; Reinoso, Eduardo
The simplicity, timeliness, and reliability of a post-earthquake assessment are fundamental for decision-makers in emergency management. An adequate risk assessment will help during the recovery and, therefore, increases the resilience of the community. Although within this context, the walk-down damage survey with the correct filling of evaluation forms and use of processing-data tools make possible a pertinent post-earthquake assessment, it is desirable to have measurable parameters that can complement the visual field evaluation with quantitative information. In some cases, basic quantitative measures, such as crack width, are not enough to make pertinent structural damage assessments. This article presents a fast and simple methodology to estimate the median maximum displacement and plastic energy demands on simple single-degree-of-freedom systems from the residual displacement they exhibit after being subjected to ground motions generated in the lakebed zone of Mexico City. Based on this, a discussion is offered on how a post-earthquake assessment can be improved by complementing the visual and measured information gathered on an existing structural system after an intense ground motion, with estimates of its maximum and cumulative plastic deformation demands derived from its residual deformation.